Brand Journalism Approach in Corporate Communication of Educational Organization - Yarnykh, Veronika (International Journal of Mass Communication, 2023)
Nowadays we see the principal fast changes in the Internet space. We live in media world and this factor make strong effect on all aspects of our life. Educational organizations are also the part of this new world and they have to change not only within the media space but also, according to changes in the social life. Social communication and new generations in social space asks about new methods, technologies and tools of communication between educational organization and its stakeholders. Brand journalism as rather new approach lets to find new technologies and tools in corporate communication of educational organization. Such tools as using the webtools of educators and their personal public for creating the positive media image for example gives additional opportunities for educational organizations. This is confirmed by the research. Also, the increasing of competition makes educational organizations to react on new circumstances in the market. Considering all of the above brand journalism can be new opportunity to form effective communication for educational organizations and as a result the increasing of their competition attractiveness. The tools and technologies of brand journalism work to create a positive media image and build brand awareness. Brand journalism allows a modern educational organization to use its own corporate media more efficiently. As well as such tools of brand journalism as the formation of a community of graduates, strengthening the news agenda of an educational organization, the use of teachers and students in video content allows you to create and strengthen a positive media image.